2023
DOI: 10.1186/s12912-023-01534-z
|View full text |Cite
|
Sign up to set email alerts
|

Research on the learning experience of virtual simulation class experimental teaching and learning based on the perspective of nursing students

Yazhuo Gao,
Xuehua Zhu

Abstract: Background The enrichment of information technology has impacted traditional teaching modes. The emergence of virtual simulation class experimental teaching software has effectively improved the quality of nursing experiment teaching. The learning experience of virtual simulation class experiment teaching and learning based on the perspective of nursing students is explored to provide a basis for improving related learning effects in the future. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…This study found that nursing students generally held a positive attitude toward virtual simulation systems. Consistent with the results of other studies, all nursing students found the virtual simulation system as a novel, flexible, and interesting learning tool, which could help them familiarize themselves with the different scenarios encountered in nursing practice [ 41 ]. Virtual simulation systems provide nursing students with a realistic and immersive environment to improve the efficiency of theoretical knowledge transfer, without any barriers of time or space [ 42 ].…”
Section: Discussionsupporting
confidence: 82%
“…This study found that nursing students generally held a positive attitude toward virtual simulation systems. Consistent with the results of other studies, all nursing students found the virtual simulation system as a novel, flexible, and interesting learning tool, which could help them familiarize themselves with the different scenarios encountered in nursing practice [ 41 ]. Virtual simulation systems provide nursing students with a realistic and immersive environment to improve the efficiency of theoretical knowledge transfer, without any barriers of time or space [ 42 ].…”
Section: Discussionsupporting
confidence: 82%